Examination of the Levels of Internet Addiction According to the High School Students' State of Doing Sports - Şenbakar, Kubilay; Sezer, Süreyya Yonca; Taş, Orhan (Tamer KUTLUCA, 2025)
The objective of our research is to look at the internet addiction levels of high school pupils based on their athletic status. In our investigation, we employed the survey model. This study's universe includes of high schools in the province of Elazig. Elazig's Fırat Anatolian High School, Elazig Fine Arts High School, Elazig Sports High School, and Mehmet Akif Ersoy Anatolian High School comprise its sample. A total of 135 students from these high schools, 64 male and 71 female, volunteered to participate. Our research is divided into two parts. The personal information form was employed in the first section, and the internet addiction scale was used in the second. The scale, created by Young and shortened by Pawlikowski et al., consists of 12 components. Following the collection of study data, the SPSS 22.0 statistical package application was employed. As a result of our research, the average score on the internet addiction scale was higher than the national average, and no statistically significant difference was found in the variables of your gender, class, type of school, frequency of doing sports, type of sport, and frequency of weekly exercise. When the average internet addiction scores of high school students are examined; it is discovered that women's scores are high in terms of frequency of doing sports and it has been determined that the internet addiction scores of those who never do sports, do not do sports and do at least sports a week have higher internet addiction scores. As a result of this research, it was determined that the internet addiction levels of high school students who do not do sports are higher than their peers who do sports regularly.
Keywords: Development of Physical Education and Education Programs; Beden Eğitimi ve Eğitim Programlarının Geliştirilmesi